Lingkungan Internal, Lingkungan Eksternal, dan Rahasia Jiwa Kewirausahaan sebagai Landasan Strategi Diferensiasi, serta Pengaruhnya terhadap Keunggulan Bersaing Usaha Mikro Tanaman Hias di Kota Denpasar - RIA NURLINA, NLP.; SUPARTA, N.; SUTJIPTA, N. (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
This study aims to examine and explain the influence of the internal environmental, external environment, and the soul of enterpreneurship secret of the strategy differentiation and their competitive advantage. The Study was conducted on small medium enterprises (SME) of ornamental plants located in the city of Denpasar based on data obtained from the Department of Agriculture and Horticulture Denpasar. Sampel study was determined using 67 business units, and selected using methods of proportional sampling with the owners as respondents. Entire data obtained from the distribution of research instruments were used for analysis. Furthermore, the data were analyzed using structural equation model (SEM) also known as variance-based Partial Least Square (PLS). The results showed that the internal control environment and the soul of enterpreneurship secret are important basis for micro-entrepreneurs in the preparation of differentiation strategy, according differentiation strategies are capable and properly applied to increase in competitive advantage. Differentiation strategy is a key mediator integrating internal control environment and the secret  of entrepreneurial spirit to generate increased competitive advantage. Meanwhile the soul of enterpreneurship secret is a another important capability in the implementation of the differentiation strategy to achieve greater competition. Interesting finding, the external environment is a direct determinant of competitive advantage. The implementation of the differentiation strategy based on internal and secret environment entrepreneurial spirit, and together with the support of the external environment are attribute to the success of micro-entrepreneurs  to archieve competitive advantage.
Keywords: internal environment, external environment, entrepreneurial secret, differentiation strategy, and competitive advantage.